The Effect of Audio-Assisted Reading on Incidental Learning of Present Perfect by EFL Learners - Nushi Musa; Jahanbin Peyman (De Gruyter, 2024)
This study applies audio-assisted reading (AAR), a technique that provides multimedia input, to encourage incidental learning of the present perfect tense. The decision to choose this tense was informed by previous studies, which have shown that its multifunctional nature presents EFL learners with considerable challenges. Thirty-four Iranian EFL learners recruited through convenience sampling participated in this eight-week-long research. The learners were assigned to the experimental and control groups. The experimental group received the AAR instruction while the control group received reading-only instruction. The analysis of the data collected through pre-test, post-test, and delayed post-test indicated that the learners not only learned the target grammar structure significantly better through AAR, but also retained it longer. The findings of the study and the implications for language teaching and learning are discussed.